Pandangan Studi Gender Terhadap Transgender - Amelia, Nanda; Susilawati; Erta Marni Miranti; Sarmauli (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to examine the position of transgender individuals from a gender studies perspective. The research method used in this study is qualitative, using a literature review approach, collecting studies from various sources and sorting them into a narrative related to transgender. Based on the discussion of gender studies perspectives on transgender individuals, it can be concluded that transgender individuals are part of a human identity that is recognized both socially and culturally. This perspective in gender studies rejects essentialist views that only categorize identities into male and female, emphasizing that gender is a dynamic social construct. This aligns with Judith Butler's thinking in her work *Gender Trouble*, which states that gender is performative, formed through social interaction, and not solely the result of biological factors. Therefore, transgender individuals should be understood as expressions of normal human diversity, not as deviations from the norm.